Pemodelan Desain Modular Hunian Sementara Berbasis Lokalitas Material di Desa Hargotirto, Kecamatan Kokap, Kabupaten Kulon Progo - Ivan Christian; Henry Feriadi (ATRIUM: Jurnal Arsitektur, 2022)
Title: Modeling Temporary Shelter Modular Design Based on Material Locality in Hargotirto Village, Kokap District, Kulon Progo Regency   Hargotirto village has an area that is prone to landslides. Several times the landslides caused the affected communities to be forced to flee to temporary shelters with several problems, such as the absence of private space for refugees and the lack of supporting facilities. The modular temporary shelter model developed through this research is expected to create advantages in terms of provision, time, and quality. The modeled temporary housing also considers local elements such as local building architecture, craftsman skills, and local materials obtained from local raw materials. Material locality data were collected through field observation surveys and guided interviews with residents and builders. The research method used is simulation and modeling research through modeling the form of temporary housing that considers the use of local materials such as wood and bamboo, the strength of modular construction, and variations in space requirements. To check the structural strength and construction details of each developed model using SAP2000 software. Several alternative models have been developed, taking into account the availability of local materials, the condition of the land area, and a series of modules in the form of single or row shelters that provide shared space for refugees.